El Salvador Financial Sector Assessment Program Update : Payments, Remittances, and Securities Settlement Systems - International Monetary Fund; World Bank (Washington, DC, 2017)
Payment systems are a core part of all financial systems. The quality of payment systems determines the stability of the overall economy, the efficiency and reliability of financial intermediation, and the possibility for the private sector to innovate and provide new services to consumers. This technical note presents the results of the assessment of payments, remittances, and securities settlement processes in El Salvador, based on international standards and best practices. It includes several observations for the improvement of the National Payments System (NPS) in El Salvador. This note takes into account the peculiarities of the jurisdiction of El Salvador: namely, the relatively small size of the financial system and the dollarized nature of the economy. The central bank and other institutions are already planning appropriate actions on many of the issues discussed. In some cases, however, the team identified additional elements, which are discussed in this note.